Estudio socioeconómico de la parroquia 24 de mayo y su relación con el desarrollo comercial, cantón Quevedo período 2006-2012 - Meza Martínez, Johanna Elizabeth (2014)
This socioeconomic study aims to identify the sources of income of households in the Parish May 24, determine the quality of life and meet the economic development in terms of infrastructure during 2006-2012. Since in this parish there is no similar study to meet the needs presented by the authorities. The Parish May 24 Quevedo located in Canton, with 17,925 inhabitants according to the INEC. (National Institute of Statistics and Census) 2010, surveys and interviews were conducted to examine the importance of socio economic factors in relation to their commercial development. The methods used in the socio-economic study are historical, inductive, analytical observational and field work was conducted through home visits and various businesses established in the parish. Which concluded that 52.5% of households have an average income between $ 319.00 to $ 636.00, plus the parish May 24 is partially equipped with all the basic facilities and 98.1 % of the population is economically active. The authorities of the parish is able to manage socio economic study basic and important requirement to the benefit of the citizens.